(untitled) (Informatica, 2024)
In a variety of areas, including healthcare, banking, and manufacturing, repetitive and rule-based processes are automated using robotic process automation (RPA), a fast developing technology. An overview of RPA’s, its uses, limitation, and applications are given in this paper. RPA can lower costs, increase process speed, accuracy, and efficiency, and free up staff to concentrate on jobs of higher value. RPA is frequently used for tasks including data input, billing, and customer care. RPA can’t, however, execute activities that call for human judgment, decision-making, or creativity, for instance. The adoption of RPA also needs a sizable initial investment and continual maintenance. This paper also touches on a few RPA-related ethical issues, like employment displacement and data privacy. While RPA has a great deal of promise to alter sectors, its deployment can only be successful if its limitations and ethical implications are carefully considered.